Characteristics explaining performance in downhill mountain biking - Chidley, J. B.; MacGregor, A. L.; Martin, C.; Arthur, C. A.; Macdonald, J. H. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To identify physiological, psychological, and skill characteristics that explain performance in downhill (DH) mountain-bike racing. Methods: Four studies were used to (1) identify factors potentially contributing to DH performance (using an expert focus group), (2) develop and validate a measure of rider skill (using video analysis and expert judge evaluation), (3) evaluate whether physiological, psychological, and skill variables contribute to performance at a DH competition, and (4) test the specific contribution of aerobic capacity to DH performance. Results: Study 1 identified aerobic capacity, handgrip endurance, anaerobic power, rider skill, and self-confidence as potentially important for DH. In study 2 the rider-skill measure displayed good interrater reliability. Study 3 found that rider skill and handgrip endurance were significantly related to DH ride time (ß = -0.76 and -0.14, respectively; R2 = .73), with exploratory analyses suggesting that DH ride time may also be influenced by self-confidence and aerobic capacity. Study 4 confirmed aerobic capacity as an important variable influencing DH performance (for a DH ride, mean oxygen uptake was 49 ± 5 mL/kg·min, and 90% of the ride was completed above the 1st ventilatory threshold). Conclusions: In order of importance, rider skill, handgrip endurance, self-confidence, and aerobic capacity were identified as variables influencing DH performance. Practically, this study provides a novel assessment of rider skill that could be used by coaches to monitor training and identify talent. Novel intervention targets to enhance DH performance were also identified, including self-confidence and aerobic capacity.